Pengaruah Layanan Bimbingan Kelompok Dengan Teknik Modelling Terhadap Kedisiplinan Kerja Pada Karyawan Astra Motor Gajahmada - Sherlina Annisa Yulianti Yulianti; Heri Saptadi Ismanto; Siti Fitriana (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study aims to determine the effect of group guidance services using modeling techniques on work discipline among employees at Astra Motor Gajahmada Semarang. The background of this research is the importance of work discipline as one of the factors that influence productivity and efficiency in the company. This research uses a quantitative approach with a one-group pretest-posttest design. The sample consists of 30 employees selected through simple random sampling. Data was collected through a work discipline scale questionnaire that has been tested for validity and reliability. The analysis technique used is the t-test with the aid of SPSS. The results of the study show that there is a significant effect of group guidance services using modeling techniques on the improvement of employee work discipline. Where the results of the hypothesis test that have been carried out in this study are known that the results of tcal = 10.45 > 1.706 ttables. then Ho was rejected and Ha was accepted. So the hypothesis reads